Ni nanoparticles highly dispersed on ZrO2 and modified with La2O3 for CO methanation. Issue 15 (1st February 2016) - Si, Jing; Liu, Guilong; Liu, Jingge; Zhao, Lin; Li, Shuangshuang; Guan, Yi; Liu, Yuan
Abstract : To improve the anti-sintering and anti-carbon deposition ability of the supported metallic nano catalysts, a new scheme for designing and preparing catalysts for CO methanation is presented in this work. Abstract : To improve the anti-sintering and anti-carbon deposition ability of the supported metallic nano catalysts, a new scheme for designing and preparing catalysts for CO methanation is presented in this work. In the scheme, a series of x LaNiO3 /ZrO2 ( x = 15%, 20%, 25%) catalysts were prepared according to the citrate complexing method. The catalysts were characterized by using BET, XRD, H2 -chemisorption, H2 -TPR, and TEM technologies. After reduction, the LaNiO3 /ZrO2 catalyst precursor preferred to form Ni nanoparticles highly dispersed on ZrO2 and modified with La2 O3 . Compared with the catalyst prepared by the traditional impregnation method, the Ni/La2 O3 –ZrO2 derived from LaNiO3 /ZrO2 showed a higher dispersion of Ni on ZrO2 and exhibited higher CO conversion and CH4 selectivity. Meanwhile, the LaNiO3 /ZrO2 catalyst showed excellent stability owing to the significant improvement in both anti-carbon deposition and anti-sintering. The catalyst prepared according to this scheme intensified the interaction between Ni and La2 O3, thus favoring the synergistic effect of La2 O3 and Ni, which led to the high dispersion of Ni nanoparticles as well as the very good anti-sintering and anti-carbon deposition ability.